What influences birth place preferences, choices and decision-making amongst healthy women with straightforward pregnancies in the UK? A qualitative evidence synthesis using a 'best fit' framework approach - Kirstie Coxon; Alison Chisholm; Reem Malouf; Rachel Rowe; Jennifer Hollowell (BMC, 2017)
Abstract Background English maternity care policy has supported offering women choice of birth setting for over twenty years, but only 13% of women in England currently give birth in settings other than obstetric units (OUs). It is unclear why uptake of non-OU settings for birth remains relatively low. This paper presents a synthesis of qualitative evidence which explores influences on women's experiences of birth place choice, preference and decision-making from the perspectives of women using maternity services. Methods Qualitative evidence synthesis of UK research published January 1992-March 2015, using a 'best-fit' framework approach. Searches were run in seven electronic data bases applying a comprehensive search strategy. Thematic framework analysis was used to synthesise extracted data from included studies. Results Twenty-four papers drawing on twenty studies met the inclusion criteria. The synthesis identified support for the key framework themes. Women's experiences of choosing or deciding where to give birth were influenced by whether they received information about available options and about the right to choose, women's preferences for different services and their attributes, previous birth experiences, views of family, friends and health care professionals and women's beliefs about risk and safety. The synthesis additionally identified that women's access to choice of place of birth during the antenatal period varied. Planning to give birth in OU was straightforward, but although women considering birth in a setting other than hospital OU were sometimes well-supported, they also encountered obstacles and described needing to 'counter the negativity' surrounding home birth or birth in midwife-led settings. Conclusions Over the period covered by the review, it was straightforward for low risk women to opt for hospital birth in the UK. Accessing home birth was more complex and contested. The evidence on freestanding midwifery units (FMUs) is more limited, but suggests that women wanting to opt for an FMU birth experienced similar barriers. The extent to which women experienced similar problems accessing alongside midwifery units (AMUs) is unclear. Women's preferences for different birth options, particularly for 'hospital' vs non-hospital settings, are shaped by their pre-existing values, beliefs and experience, and not all women are open to all birth settings.